Effect of Planting Density on the Growth of Rubber in The Vellanikkara Estate - Karthikeyan KV (Department of Plantation Crops and Spices, College of Horticulture, 1993)
The present observations on the influence of different planting densities on the performance of two clones namely RRII 105 and RRII 118 are in conformity with the results of other field experiments reported earlier. In lower planting densities, trees produced good girth, high yield per tree, thick virgin bark and high rubber content. Whereas, high planting densities contributed to poor tree girth, high yield per tree, thick virgin bark and high rubber content. Whereas , high planting densities contributed to poor tree girth, thin virgin bark and lower yield per tree. However, planting density is dependent on various other factors viz. topography of the land, system of planting to be adopted, the planting materials, cost of labour and price of rubber. Anyway, a comprise between labour cost and rubber price is needed. As far as small holders are concerned, a higher stand per hectare is preferred, since the question of labour does not arise. Therefore, for small holding sector a higher stand is recommended in order to get high per hectare yield. But there should be an optimum stand. In Malaysia, for small holders having available family labour, a planting density of approximately 740 trees per hectare is recommended. However, indepth studies are required for a meaningful recommendation in our country.